GERAKAN BINA BALITA “SEHAT” DALAM PENCEGAHAN STUNTING DI DESA TELUK KENIDAI KABUPATEN KAMPAR - Alyensi, Fatiyani; Laila, Ani; Susanti, Ari (EBIMA : Jurnal Edukasi Bidan di Masyarakat, 2024)
Abstract The National Population and Family Planning Agency (BKKBN) of Riau Province continues to optimize the Toddler Family Development (BKB) program to avoid an increase in stunting or failure to thrive in children under five in Riau Province. Based on a preliminary study by conducting interviews with the responsible midwife in Teluk Kenidai village, it was stated that a Bina Toddler (BKB) has been formed called the "Healthy" BKB with age groups 0-1 years, 1-2 years, 2-3 years and 4-5 years. year. However, the implementation has not run optimally with the Covid 19 Pandemic which has been going on for two years, making activities not run optimally. Based on data from the recording of "Healthy" BKB cadres in March 2022, there were 16 toddlers who visited the Posyandu in the 0-1 year age group, 22 people aged 1-2 years old, 20 people aged 2-3 years old and 4 years old. -5 years totaling 3 people. The implementation time is February to August 2022 with the participants of the activity are "Healthy" BKB Cadres in Teluk Kenidai Village, totaling 30 people. Methods with lectures and questions and answers as well as demonstrations in the practice of breastfeeding and making MP ASI as well as monitoring and evaluation. The results of the activity are an increase in the knowledge and skills of Healthy BKB Cadres and the development of families of Toddlers in Teluk Kenidai Village, the Working Area of ​​the Mining Health Center, Tambang District, Kampar Regency as an effort to prevent stunting Keywords: Toddler Development, stunting prevention